Relationship Between Awareness on Digitalization of Halal Management System and Product Innovation at SMEs - Abdul Rejab, Muhammad Firdaus; Azizan, Anim Zalina (Research in Management of Technology and Business, 2026)
In the increasingly competitive global halal market, Small and Medium Enterprises (SMEs) are required to leverage digital technologies to enhance compliance, efficiency, and innovation. This study examines the relationship between awareness of Digital Halal Management Systems (HMS) and product innovation among halal-certified SMEs in Batu Pahat, Johor. A quantitative research approach was employed using a structured questionnaire distributed to 125 halal-certified SMEs selected through purposive sampling. Data was analyzed using SPSS through descriptive statistics, reliability analysis, normality testing, and Spearman’s rank correlation. The findings indicate that SMEs demonstrate a high level of awareness of digital halal management systems (M = 4.28) and product innovation (M = 4.47). The results further reveal strong and statistically significant positive relationships between awareness dimensions digitalization, market expansion, efficiency and sustainability, and education and training and product innovation (ρ < 0.01). These findings suggest that higher awareness of digital halal systems is associated with greater innovation capability among halal SMEs. The study contributes empirical evidence to the halal digitalization literature and provides practical insights for policymakers and SME support agencies to strengthen digital readiness and innovation performance in the halal SME sector.